Предмет: Алгебра, автор: gdhdbdydbyrbdb24p4

Помогите пожалуйста!!! ​

Приложения:

Ответы

Автор ответа: smoljanov13
0

Ответ:

1: -4

2: 1

Объяснение:

1) ( c - 3 )² - ( c + 4 )² = 49

( c - 3 - ( c + 4 ))( c - 3 + c + 4 ) = 49

( c - 3 - c - 4 )(c - 3 + c + 4 ) = 49

-7(2c+1) = 49

-14c - 7 = 49

-14c = 56

c = -4

2)  4a²( 2a - 3 ) - (2a - 1)³ = -5

8a³ - 12a² - (8a³ - 3*4a² + 3*2a - 1) = -5

8a³ - 12a² - 8a³ + 12a² - 6a + 1 = -5

-6a = -6

a = 1

Похожие вопросы
Предмет: Русский язык, автор: Kreol